Detection of DENV-2 and Insect-Specific Flaviviruses in Mosquitoes Collected From Jeddah, Saudi Arabia - Fang, Yuan; Tambo, Ernest; Xue, Jing-Bo; Zhang, Yi; Zhou, Xiao-Nong; Khater, Emad I. M. (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Mosquito-borne diseases are rapidly spreading due to increasing international travel and trade. Routine mosquito surveillance and screening for mosquito-borne pathogens can be early indicators for local disease transmission and outbreaks. However, arbovirus detection in mosquito vectors has never been reported in Saudi Arabia. Methods: We collected 769,541 Aedes and Culex mosquitoes with Black Hole traps during routine mosquito surveillance in the first half of 2016. Cx. quinquefasciatus and Ae. aegypti were the most prevalent species observed. 25 and 24 randomly selected pools of Ae. aegypti and Cx. quinquefasciatus, respectively, were screened for arboviruses by RT-PCR. Results: DENV-2 virus and four strains of insect-specific flaviviruses, including one of cell-fusing agent virus (CFAV) and three of Phlebotomus-associated flavivirus (PAFV) were detected in pools of Ae. aegypti. We also detected 10 strains of Culex flavivirus (CxFV) in pools of Cx. quinquefasciatus. Phylogenetic analysis using whole genome sequences placed the DENV strain into the cosmopolitan 1 sub-DENV-2 genotype, and the CxFVs into the African/Caribbean/Latin American genotype. These analyses also showed that the DENV-2 strain detected in the present study was closely related to strains detected in China in 2014 and in Japan in 2018, which suggests frequent movement of DENV-2 strains among these countries. Furthermore, the phylogenetic analysis suggested at least five introductions of DENV-2 into Saudi Arabia from 2014 through 2018, most probably from India. Conclusions: To our knowledge, this study reports the first detection of arboviruses in mosquitoes in Saudi Arabia, and shows that DENV, CFAV, PAFV, and CxFV are co-circulating in Jeddah. Our findings show a need for widespread mosquito-based arbovirus surveillance programs in Saudi Arabia, which will improve our understanding of the transmission dynamics of the mosquito-borne arboviruses within the country and help predict the risk of human infections and outbreaks.